Characterisation of the prokaryotic elongation factor-Tu with structural mass spectrometry - Baines, Cameron (2025)
The elongation factor EF-Tu is an essential and ubiquitous component of prokaryotic mRNA translation. It is directly responsible for the transport of aminoacyl-tRNA to the actively translating ribosome. EF-Tu is a translational GTPase, classically thought to have two conformational extremes induced by the binding of either GDP or GTP, the open and closed conformations respectively. It is now hypothesised that, in solution, EF-Tu does not adopt these binary conformations and instead samples a wide range of conformations, with the average becoming more open or closed depending on the bound nucleotide. As an essential prokaryotic protein, EF-Tu presents itself as a desirable antimicrobial target. The elfamycins are a group of bacteriostatic antimicrobials specifically targeting EF-Tu, acting predominantly in one of two ways. Kirromycin-like elfamycins lock EF-Tu in the closed confirmation irrespective of GTP hydrolysis, preventing EF-Tu dissociating from the ribosome. Pulvomycin-like elfamycins simply prevent the binding of tRNA to EF-Tu, acting as a competitive inhibitor.